MENILAI PERAN KETIMPANGAN DAN INDEKS PEMBANGUNAN MANUSIA DALAM PERTUMBUHAN EKONOMI REGIONAL: STUDI KASUS PROVINSI JAWA BARAT, INDONESIA - Arya Pramaditya, Yudhistira; Bintang Karisma, Dikri; Muhammad Naufal, Vieri (Creative Research Journal, 2024)
Research shows that inequality could hamper economic growth, while HDI improvement generally correlates positively with economic growth. West Java, one of the provinces with the largest population in Indonesia, faces unique challenges in the interplay of relationships between those factors. This study aims to measure the relationship between measurements of inequality and the various indices that serve as components of HDI on the one hand, as well as economic growth on the other hand, in all of the 27 municipalities (i.e., regencies and cities) of West Java Province. Using panel regression of cross-sectional and time series data, this study found that inequality and the life expectancy index both showed positive and significant relationships with economic growth. These findings might be related to increased investments by wealthier individuals and increased labor productivity due to a healthier workforce. Conversely, the education and income index were found to be non-significant, possibly due to qualitative disparities in education and mismatches with labor market needs, and also due to the limitations of expenditure-based measures in regions with substantial informal economic activities that are not fully captured in official data. These findings can guide targeted interventions to balance growth and equity in West Java.